Biosafety guidelines and safety in Faculties of Veterinary Science, Argentina (Veterinary Science, 2017)
The biosafety and labor constitute topics of fundamental importance in the exercise of the veterinary profession. Having as objectives to know the situation of teaching of this topic, application of the corresponding norms as likewise to promote the establishment of programs that you/they improve the before mentioned. They were taken to end interviews and surveys to authorities, educational, students and not educational of all the national abilities of veterinary science of Argentina. They were obtained as results that none of the abilities possesses an established program as such that single 3 abilities have conformed biosafety commissions and labor security. He/she has been that the classes with better demand level toward the students and application of the norms are Microbiology, Virology, Illness Infectious and Parasitology. Most of the interviewed abilities don't include in their budget the provision of elements and/or protection teams for the personnel. In the formation of the veterinary doctor's grade it should have a deep knowledge of this problem in order to assure a good quality of professional life
Keywords: Biosafety; Labor security